CIRCKLHL2 KNOCKDOWN ALLEVIATES SEPSIS-INDUCED ACUTE LUNG INJURY BY REGULATING MIR-29B-3P MEDIATED ROCK1 EXPRESSION DOWN-REGULATION. Issue 1 (8th January 2023) - Li, Nan; Li, Yuqiang; Wu, Bin; Sun, Rongli; Zhao, Mingzhou; Hu, Zhansheng
ABSTRACT: Background: Acute lung injury (ALI) induced by sepsis is distinguished by an inflammatory progression. Herein, we investigated the action of circular RNA kelch like family member 2 (circKlhl2) in sepsis-induced ALI. Methods: The animal or cell model of sepsis ALI was established by LPS stimulation. The contents of circKlhl2, microRNA-29b-3p (miR-29b-3p), rho-associated coiled-coil containing protein kinase 1 (ROCK1), CyclinD1, B-cell lymphoma-2 (Bcl-2), and cleaved-caspase 3 (C-caspase-3) were detected by quantitative real-time polymerase chain reaction and western blot, respectively. Cell viability was assessed by cell counting kit 8 assay. Cell cycle and apoptosis were evaluated by flow cytometry. The abundances of proinflammatory cytokines were detected by enzyme-linked immunosorbent assay. Besides, the targeted relationship between miR-29b-3p and circKlhl2 or ROCK1 was verified by dual-luciferase reporter assay, RNA immunoprecipitation assay and RNA pull-down assay. Results: Loss of circKlhl2 mitigated lung injury and proinflammatory cytokine expression in sepsis-ALI mice model and alleviated LPS-induced apoptosis and inflammatory response in microvascular endothelial cell (MPVECs) in vitro . The abundances of circKlhl2 and ROCK1 were boosted, while the miR-29b-3p level was diminished in the animal or cell model of sepsis-ALI. MiR-29b-3p inhibition abrogated circKlhl2 knockdown-mediated effects on MPVECs injury. Moreover, miR-29b-3p overexpression promoted cell proliferation and inhibited apoptosis and inflammation in LPS-treated MPVECs, while ROCK1 enhancement reversed these effects. Conclusion: CircKlhl2 expedited the sepsis-induced ALI by adjusting miR-29b-3p/ROCK1 axis.